Coliform bacteria screening and evaluating chemical composition of raw milk from dairy farms of Sylhet Sadar, Bangladesh - Chowdhury, Tonmoy; Roky, Shamsul Alam; Uz-Zaman, Md. Ashik; Islam, Md. Tanvir; Mohonto, Bikash (Indian Journal of Dairy Science, 2022)
The study aims screening of coliform bacteria and evaluates chemical constituents of farm supplied raw milk at Sylhet sadar, Bangladesh. A total of 50 milk samples (5 samples from each farm) were collected from randomly selected 10 different farms. Samples were diluted (1:1000000) and bacteria cultures were done in EMB (Eosin methylene blue) agar. Further, Indole test, Methyl red test, Voges-Proskauer were done to differentiate environmental and fecal coliform (Escherichia coli). Chemical analysis of milk was done using automatic milk-analyzer. Total coliform count (TCC) was found to be ranged between 0.6 Ã— 106 to 7.8 Ã— 106 colony forming unit/ml (cfu/ml) and the biochemical tests showed negative results for Indole and Methyl red test and positive for Voges-Proskauer test, respectively confirming the absence of fecal coliform (Escherichia coli) and presence of environmental coliforms. Mean values of Chemical constituents were found to be fat% (4.48%), Solid-Not-Fat% (8.55%), Protein% (3.20%), Lactose% (4.66%) and Mineral% (0.68%). Adulteration with added water in milk was also found with a mean of 0.89%. This study will help to generate an idea about coliform contamination scenario and quality of farm milk found at the particular study area.